Parent-infant psychodynamics : wild things, mirrors and ghosts : a reader designed for a variety of professionals working with expectant parents, babies and their families, and for parents and students in pursuit of psychoanalytic understanding /: wild things, mirrors and ghosts : a reader designed for a variety of professionals working with expectant parents, babies and their families, and for parents and students in pursuit of psychoanalytic understanding. (2018) - Unknown
No abstract available